The Circadian Clock Drives Mast Cell Functions in Allergic Reactions - Christ, Pia; Sowa, Anna Sergeevna; Froy, Oren; Lorentz, Axel (Frontiers in Immunology, 2018)
Allergic diseases are known to vary in the severity of their symptoms throughout the day/night cycle. This rhythmicity is also observed in mast cell function and responsiveness. Mast cells are key effector cells of allergic reactions and release cytokines, chemokines, and important inflammatory mediators such as histamine which have been shown to display diurnal variation. Recent research clarified that mast cells are controlled by their internal clock - which is regulated by a specific set of clock genes - as well as external factors such as light sensed by the suprachiasmatic nuclei, hormonal status, or diet. Here, we give an overview of the connections between circadian clock, mast cells, and allergic disease. Further work aimed at studying the role of chronotherapy/chronomedicine should take into account this rhythmic nature of not only mast cells but also the immune responses generated by mast cell signaling.